PENINGKATAN KEMAMPUAN KOGNITIF MELALUI PERMAINAN PECAH TELUR PADA ANAK KELOMPOK A DI RA SHODRUL ULUM AL-CHOLIL BRONGKAL PAGELARAN-MALANG - Zamzami, Yulia; Sari, Ratih Permata (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2019)
The process of increasing children's cognitive abilities in learning is very important to be developed through the process of game activities. The purpose of this research is to describe the improvement of cognitive abilities by using the game of breaking eggs in group A children and to describe the application of the game of breaking eggs that can improve cognitive abilities in children of group A. This research uses a class action research (Action Research) using two cycles applied in RA children in group A. The results of the study in the first cycle showed an increase in cognitive abilities in recognizing the concept of numbers but still had not reached maximum results with a percentage of 43.13%. Meanwhile, the results of research in the second cycle have shown the development of cognitive abilities in recognizing the concept of numbers with a percentage of 79.40%. The final results of an average increase between the two cycles reached 36.27%. The research can be concluded that the increase between the two cycles is influenced by the presence of a broken egg in the form of a game concept in the cognitive learning process of early childhood..